Resilience-related Breast Cancer: A Concept Analysis - Fitria Endah Janitra; Nur Aini; Anggi Lukman Wicaksana (Nurse Media: Journal of Nursing, 2023)
Background: Breast cancer-related adversity can result in severe psychological issues. However, some patients were able to demonstrate resilience, while others were not. Therefore, the concept of resilience in breast cancer patients requires further clarification.